Gabapentin improves colonic inflammatory damage and oxidative stress on acetic acid-induced colitis independent of cannabinoid pathway (Research, Society and Development, 2021)
Objective: Gabapentin (GBP) possess a systemic anti-inflammatory action confirmed and endocannabinoids system have been effectives in reduces inflammatory disorders on intestinal tract. The aim of this study is evaluate the participation of the endogenous cannabinoids pathway in the anti-inflammatory and antioxidant effects of GBP in acetic acid (AA) induced colitis in mice. Methods: Colitis induction was performed using AA (6%) and mice treated intraperitoneally with GBP or dexamethasone (subcutaneously) at 17 h or 17:30 h after induction of colitis, respectively. After 18 h of colitis induction, the animals were euthanized and colonic sample was taken for evaluation of macroscopic and microscopic lesion, wet weight and biochemical analyzes. Results: The administration of GBP was effective in reduce the macro and microscopic lesions, significant decreasing the colonic wet weight of colitis mice. The drug reduced the concentration myeloperoxidase (MPO), malondialdehyde (MDA) and interleukin 1 (IL-1) and increased the level glutathione (GSH) in colitis mice compared to normal mice. The treatment with endocannabinoids (ECs) receptors antagonists did not alter the GBP effect. Conclusion: Gabapentin was able to reduce inflammatory parameters in acid acetic-induced colitis, but its effect seems to be independent of cannabinoid pathway.